alguém pode me ajudar nessas questões por favor!!
Anexos:
![](https://pt-static.z-dn.net/files/df0/e47fbfafc3c00026c449a1fb6f745c29.jpg)
![](https://pt-static.z-dn.net/files/df6/0b9fd6efa476a60ce65e7521ab0656e2.jpg)
Soluções para a tarefa
Respondido por
1
Explicação passo-a-passo:
1)
f( g ( x ) ) =
f ( 6x + 8 ) = 2 • ( 6x - 8 ) - 5
f ( g( x ) ) = 12x - 16 - 5
f ( g ( x ) ) = 12x - 21
opcão B
2) g ( f ( x ) ) =
g ( 2x - 5 ) = 6 • ( 2x - 5 ) + 8
g ( f ( x ) ) = 12x - 30 + 8
g ( f ( x ) ) = 12x - 22
opcão A
Perguntas interessantes
Geografia,
9 meses atrás
Geografia,
9 meses atrás
Biologia,
9 meses atrás
História,
1 ano atrás
Inglês,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás